Thinking Through New Methodologies. Sounding Out the City With Teenagers - O’Keeffe, Linda (Qualitative Sociology Review, 2015)
This paper explores the place for sound within social theory, more specifically, how sound as a subject can be interpreted methodologically. The paper examines the various methods implemented within a Ph.D. research project. The research adopted a participatory approach, examining the missing voices in the post design of place. In this way, the research focused on those groups often excluded in the design of urban space, teenagers. The methods included participant documented soundwalking, sound mapping, focus groups, and ethnographic soundwalks. This paper argues that a closer attention to sound, when examining the urban area, will help shape one’s understanding of the everyday. Methods that explore sound as part of the makeup of social life, either as place building or space making, whether they are politically intentional or historically relevant, need to be advanced.